Review: Attachment Devices of Insect Cuticle - Ågren, Lennart (Entomologica Fennica, 2002)
Gorb, S. 2001: Attachment Devices of Insect Cuticle. Kluwer Academic Publishers, Dordrecht/Boston/ London. 305 pages. ISBN 0-7923-7153-4.